The Left-Handed Child and Learning Difficulties - Zăvoianu, Elena Ancuta; Ciucă, Simona Gabriela (Technium Social Sciences Journal, 2023)
School education plays an essential role in the formation and development of the child's personality, and due to this fact it is necessary that the educational process be adapted to the requirements of all children, whether they are normal or with special educational requirements, right-handed or left-handed. Due to the predominance of the right cerebral hemisphere these children process information differently. However, the entire school curriculum is designed for children who are left-hemisphere dominant. Thus the right hemisphere is little used, while the left hemisphere is overworked. In the case of left-handed children, this fact generates learning difficulties, due to the fact that most educational activities fail to highlight their abilities, which are different from those of other students. We must draw attention to the fact that a left-handed child is not a child with an intellectual disability, but an inflexible educational system can turn a biological peculiarity such as left-handedness into a handicap. This paper deals with the problems that the left-handed child may have in the educational setting, especially due to the specific learning difficulties that may arise. Approaching the problem through the analysis of learning styles will help us to develop a series of methods and activities that will value them.